PERUBAHAN POLA KONSUMI PANGAN LOKAL KE BERAS PADA PENERIMA PROGRAM KELUARGA HARAPAN (PKH) DI KOTA KENDARI - Asnaity, Eva; Aso, La; Syahrun, Syahrun (Universitas Halu Oleo, 2021)
The objective of this study is to describe the local food consumption patterns of the recipients of the Family Hope Program (PKH). The theory used for reading data is the thinking of Levi Strauss on the Culinary Triangle and Kingsley Davis (1990) on Social Change. This research used qualitative data, where primary data was obtained through observation and in-depth interviews with informants and field notes, then all research objects were analyzed descriptively qualitatively. The results of research showed that the changes in local food consumption patterns of rice for the recipients of the Family Hope Program have experienced a change in that they used to consume local food more often with the assistance program from the government making the community's dependence on rice commodities, besides that people's taste for rice consumption is influenced because the taste of rice is better. than nice.Keywords: Consumption patterns, local food, recipients of the hopeful family program (PKH)